CARDIOTOXICITY OF ANTINEOPLASTIC THERAPY – UNDERLYING MECHANISMS, CLINICAL MANIFESTATIONS, AND BASIC PRINCIPLES OF CARDIO-ONCOLOGY: Cardiotoxicity of cancer treatment - Cvetković, Zorica; Marković, Olivera; Mitrovic, Mirjana (Srpski medicinski časopis Lekarske komore, 2023)
Malignancies and cardiovascular diseases are the most common cause of morbidity and mortality in the modern world. Taking into account the ageing population of developed countries and the fact that malignancies are mainly diseases of old age, the projected increase in the incidence of malignancies in the countries of the European Union, by 2040, is more than 20%. Modern, personalized therapy of malignant diseases, which has significantly improved the prognosis and survival of hemato-oncology patients, requires careful ambulatory patient follow-up, in order to prevent, timely diagnose and adequately treat the immediate and delayed adverse effects of antineoplastic therapy. The cardiovascular system is particularly sensitive to antineoplastic agents due to its particular structure and functions. A personalized and multidisciplinary approach in the treatment and follow-up of hemato-oncology patients has led to the development of a new subspeciality – cardio-oncology, whose main task is the early identification of oncological patients, with or without associated cardiovascular disease, who have an increased risk of developing cardiotoxicity during antineoplastic treatment. The article describes the basic mechanisms of cardiotoxicity of the most important groups of antineoplastic drugs, clinical manifestations as well as contemporary recommendations for primary and secondary prevention.